High‐Performance Dibenzoheteraborin‐Based Thermally Activated Delayed Fluorescence Emitters: Molecular Architectonics for Concurrently Achieving Narrowband Emission and Efficient Triplet–Singlet Spin Conversion. (25th June 2018) - Park, In Seob; Matsuo, Kyohei; Aizawa, Naoya; Yasuda, Takuma
Abstract: Thermally activated delayed fluorescence (TADF) materials, which enable the full harvesting of singlet and triplet excited states for light emission, are expected as the third‐generation emitters for organic light‐emitting diodes (OLEDs), superseding the conventional fluorescence and phosphorescence materials. High photoluminescence quantum yield ( Φ PL ), narrow‐band emission (or high color purity), and short delayed fluorescence lifetime are all strongly desired for practical applications. However, to date, no rational design strategy of TADF emitters is established to fulfill these requirements. Here, an epoch‐making design strategy is proposed for producing high‐performance TADF emitters that concurrently exhibiting high Φ PL values close to 100%, narrow emission bandwidths, and short emission lifetimes of ≈1 µs, with a fast reverse intersystem crossing rate of over 10 6 s −1 . A new family of TADF emitters based on dibenzoheteraborins is introduced, which enable both doped and non‐doped TADF‐OLEDs to achieve markedly high external electroluminescence quantum efficiencies, exceeding 20%, and negligible efficiency roll‐offs at a practical high luminance. Systematic photophysical and theoretical investigations and device evaluations for these dibenzoheteraborin‐based TADF emitters are reported here. Abstract : A new family of thermally activated delayed fluorescence emitters based on dibenzoheteraborins is developed. These emitters enable both doped and non‐doped organic light‐emitting diodes to achieve markedly high external electroluminescence quantum efficiencies of up to 25.3% and negligible efficiency roll‐offs at a practical high luminance.